Ultrasonic-assisted Biosynthesis of Silver Nanoparticle using Green Seaweed Ulva lactuca Extract - Hardiningtyas, Safrina Dyah; Abrar, Muhammad Naufal; Ramadhan, Wahyu; Wakabayashi, Rie; Uju, Uju (:Agency for Marine and Fisheries Research and Human Resources, Indonesia, 2023)
Ulva lactuca, a green seaweed that is widely distributed in Indonesia, is abundant but still underutilized. Even though this seaweed contains a sulfated polysaccharide called ulvan as much as 30-40% of its dry biomass and secondary metabolite. These components can be applied in various fields including as a reducing agent for silver ions in the bottom up synthesis of silver nanoparticles. The utilization of seaweed extract combined with ultrasonication is expected to enhance the efficacy of environmentally friendly silver nanoparticle synthesis. The objective of this study was to obtain he crude extract of U. lactuca andto investigatethe impact of extract concentration and ultrasonication duration on the biosynthesis of silver nanoparticles. The study consists of two main phases 1) bio-synthesis employing different concentrations of the U. lactuca crude extract, and 2) bio-synthesis using selected extract concentrations combined with ultrasonic assistance for varying durations. The results of this study indicate that the crude extract of U. lactuca is a crude ulvan polysaccharide with a yield value and sulfate content of 26.9 ± 0.90% and 20.04 ± 1.02%, respectively. A reddish-brown color indicates the formation of silver nanoparticles. Based on the absorbance intensity, a 10% (v/v) concentration of ulvan crude extract produced the highest absorbance intensity (0.038 a.u). In addition, the ultrasonication duration of 60 minutes has succeeded in producing the smallest particle size (267.40 ± 6.52 nm) with a homogeneous particle distribution (PdI 0.265 ± 0.05). Scanning electron microscope (SEM) images depicted oval-shaped silver nanoparticles, while the Fourier-transform infrared (FTIR) spectrum indicated the degradation of sulfate and polysulfide functional groups in the crude extract during the biosynthesis process. These findings highlight the significant role of sulfate/sulfide groups present in the U. lactuca crude extract in the biosynthesis of silver nanoparticles.